2015
DOI: 10.1007/s11998-015-9694-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphate ion on the morphology, adhesion strength, and corrosion performance of zirconium-based surface treatment

Abstract: In this study, the effect of phosphate ion (PO 4 3À ) was investigated on the different properties of a zirconium-based nanoceramic conversion layer. At the first step, the phosphate ion concentration was optimized using the DC polarization technique. In the next step, the surface morphological aspect of the bare and treated mild steel was evaluated utilizing field emission scanning electron microscopy technique. The results indicate formation of a composite conversion coating on the mild steel surface. Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The surface free energy, calculated by the van Oss–Chaudhury–Good method, was calculated to be 18.8 mJ m −2 (Table 1). The surface energy value is significantly lower in comparison to the control surface and other reported surfaces further confirming the low adhesive nature of the super surface prepared herein 3639…”
Section: Resultssupporting
confidence: 73%
“…The surface free energy, calculated by the van Oss–Chaudhury–Good method, was calculated to be 18.8 mJ m −2 (Table 1). The surface energy value is significantly lower in comparison to the control surface and other reported surfaces further confirming the low adhesive nature of the super surface prepared herein 3639…”
Section: Resultssupporting
confidence: 73%
“…Pull-off tests, cathodic disbonding tests and EIS measurements indicated that a Zr-based coating on mild steel significantly improved adhesion of an epoxy topcoat. 56 The Zr coating increased the surface roughness (from 70 to 98 nm), which improved the adhesion of an organic topcoat and cathodic disbonding resistance as measured by EIS during 192 h in 3.5 wt% NaCl.…”
Section: Adhesion Strength and Delamination Mechanism Of The Substratmentioning
confidence: 96%
“…The pH of 4.0 was used in the vast majority of reports. 6,36,37,42,51,52,[55][56][57]61,62,65,68,75,[85][86][87][88]94,98,108,109 although conversion was carried out at pH between 1.5 and 6. 30,32,46,48,49,53,64,66,[68][69][70]77,78,82,90,95,99,106,107,110 More extensive and thicker coating formation at pH 4.0 than at 2.9 was noticed for Gardabond X4707 coating on AA6060.…”
Section: Conversion Bath Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmentally acceptable non-chromate based conversion coatings i.e. phosphate [13][14][15][16][17], molybdate [18], zirconium [19] and rare earth metal salts [20][21][22][23] have been considered in this regard.…”
Section: Introductionmentioning
confidence: 99%